Medical services quality: a case study in private institution - Leyzeaga Vargas, Mary (2014)
The objective of this study is to evaluate the quality of service perceived by users in a private medical center in Valencia, Venezuela. The instrument for data collection was based on the perceptions of SERVQUAL. Were identified by Factor Analysis, once they demonstrated the relevance sample, three (03) dimensions: Safety, Reliability and tangibility, explaining 66.63% of the total variance, likewise, the instrument showed internal consistency (alpha cronbach> 0.955) as it reliable and results of statistical tests performed (Significant at 5%), demonstrate the validity. Based on the results, we conclude that the questionnaire has enough condition to be used as a measure of the quality perceived by patients private medical center, and as an input for the design of strategies.